The microbiome as a therapeutic co-driver in melanoma immuno-oncology - Bautista, Jhommara; Villegas-Chávez, Jaime Andrés; Bunces-Larco, Doménica; Martín-Aguilera, Rafael; López-Cortés, Andrés (Frontiers in Medicine, 2025)
Melanoma, one of the most aggressive skin cancers, remains a major clinical challenge due to its high metastatic potential, therapy resistance, and rising global incidence. Although immune checkpoint inhibitors have transformed management, variable responses and acquired resistance limit durable benefit. Emerging evidence positions the microbiome as a pivotal determinant of melanoma biology and therapeutic outcomes. Dysbiosis in the skin, gut, and oral compartments fosters tumor-promoting inflammation, immune evasion, and oncogenic signaling, whereas enrichment of specific commensals, such as Akkermansia muciniphila and Faecalibacterium prausnitzii, enhances antigen presentation and effector T cell activity, improving ICI efficacy. Mechanistically, microbial metabolites, including short-chain fatty acids, tryptophan derivatives, and bile acids, modulate epigenetic programs, G-protein–coupled receptor signaling, and oncogenic cascades such as PI3K–AKT and RAS–RAF–MEK–ERK. Beyond the gut, cutaneous microbiota such as Staphylococcus epidermidis exert direct antitumor effects, while pathogenic oral taxa propagate systemic inflammation that shapes the melanoma tumor microenvironment. These insights are driving the development of microbiome-targeted interventions, including fecal microbiota transplantation, defined consortia, probiotics, and dietary modulation, with early clinical studies showing the potential to overcome resistance to immunotherapy. Integration of circadian biology further suggests that host–microbiome–immune interactions are temporally regulated, opening new dimensions for therapeutic optimization. By synthesizing mechanistic, clinical, and translational advances, this review highlights the microbiome as both a biomarker and a therapeutic axis in melanoma, underscoring its promise to transform precision immuno-oncology.